2017
DOI: 10.1108/maj-04-2016-1366
|View full text |Cite
|
Sign up to set email alerts
|

Internal auditors’ reputation and managers’ reliance decision

Abstract: Purpose The purpose of this paper is to investigate how internal auditors’ performance reputation for auditing and assurance engagements affects corporate managers’ reliance on their consulting recommendations. Design/methodology/approach This study conducted a 2 × 2 between-subjects experiment in which 103 MBA students were randomly assigned to one of the four conditions. This paper uses analysis of covariance to analyze the data. Findings The results show that internal auditors’ reputation for performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…However, if the function is ineffective and lacks good status in the organization, management will not rely on it for consulting and assurance services. The study supports Tang et al (2017), which indicates that auditing performance status has a greater impact on management's decision to depend on the IAF for assurance and consultations.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, if the function is ineffective and lacks good status in the organization, management will not rely on it for consulting and assurance services. The study supports Tang et al (2017), which indicates that auditing performance status has a greater impact on management's decision to depend on the IAF for assurance and consultations.…”
Section: Discussionsupporting
confidence: 68%
“…The results from the stakeholder perspective indicate that the value created by the IAF will lead to the implementation of IAF recommendations. Similarly, Tang et al (2017) found that managers can rely on IAF recommendations once they possess a respectable performance reputation for value creation. The quality of IAF is considered a value-added preposition (Sarens et al, 2012;Ulvi, 2015;Eulerich et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Fanning and Piercey (2014) document that managers agree more with internal auditors who organize their arguments and are likable even if an auditor's position is unsupportive of management's position. Tang et al (2017) report that internal auditor assurance engagement reputation has a positive impact on managers' reliance on consulting recommendations. No study, of which we are aware, has explored the role of internal auditor gender, communication mode and the inclusion of root cause in the communication of internal audit findings to management.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
“…Studies focusing on the IAF have examined the relationship between internal auditors and the audit committee (Goodwin, 2003;Soh and Martinov-Bennie, 2011) and between internal auditors and external auditors (Abbot et al, 2010;Prawitt, 2012;Prawitt et al, 2009). A few studies that explore management's perceptions of the IAF have evaluated management's reliance on internal auditors' consulting recommendations given their assurance reputation (Tang et al, 2017), management's assessment of IAF effectiveness in the South African public sector (Erasmus and Coetzee, 2018) and internal auditors' ability to influence management based on internal auditor's interpersonal likability, argument organization and information used in support of their position (Fanning and Piercey, 2014). However, little is known about other potential determinants of management's perceptions of the IAF.…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that self-efficacy, flexibility, perceived support from the supervisor and behavioral independence had a positive impact on internal auditors’ courage. Tang et al (2020) in a study entitled The auditor’s reputation includes the auditor’s characteristics such as moral courage and professional independence which was examined using a 2 × 2 matrix and pre-test and post-test scores. According to the findings, the internal auditors’ reputation and credibility with respect to behavioral and professional commitments improve managers’ decisions.…”
Section: Literature Reviewmentioning
confidence: 99%